Receptive vocabulary size of secondary spanish efl learners - Andrés Canga Alonso (Revista de Lingüística y Lenguas Aplicadas, 2013)
This paper responds to the need of research on vocabulary knowledge in foreign language in secondary education in Spain. Thus, this research aims at investigating (i) the receptive vocabulary knowledge of 49 girls and 43 boys, Spanish students learning English as a foreign language in a secondary school located in the north of Spain, and (ii) its pedagogical implications for students’ understanding of written and spoken discourse in English (Adolphs & Schmitt 2004; Laufer 1992, 1997; Nation 2001). We used the 2,000 frequency band of the Vocabulary Level Test (VLT) (Schmitt, Schmitt & Clapham, 2001, version 2) as the instrument to measure students’ receptive vocabulary knowledge. Our results reveal that the means of girls’ receptive vocabulary size is below 1,000 words, which agrees with the estimates proposed by López-Mezquita (2005) for Spanish students of the same age and educational level. On the contrary, the means for boys is slightly above 1,000 words, being the differences between boys’ and girls’ performance in the VLT statistically relevant. Our data also indicate that most of the students analysed in the present study could have problems to understand written and spoken discourse due to their low scores in the receptive vocabulary level test.